Peran Akademisi Dalam Peningkatan dan Penguatan Kesadaran Hukum Masyarakat Dalam Pencegahan Karhutla di Desa Sungai Tonang - Muhammad Zulhidayat; Amri Saputra; Esra Cornelius Pangaribuan; Naswa Indriyani; Faiz Habibie Chandra; Fauziah Azura; Hani Alifah; Rindu Melani; Sela Apriani; Tiara Puspita Sari; Wa Ode Nurdiani Musfirah (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
This research reveals how the role of academics can help the community in Sungai Tonang Village, Kampar Utara District, Kampar Regency, become more legally aware of how to prevent forest and land fires (karhutla). In this case, academics successfully conveyed the message of forest and land fire preventuin through a community service method that combines legal education, socialization, and local cultural approaches such as the Balimau Kasai tradition and the art of calempong baoguong music. The method used in this case in through intial data collection and direct soxialization with community leaders and village officials to addres the low legal literacy and environmental the law better, pay more attention to the environment, and have more environmental monotioring groups working to prevent forest fire. A synergistic collaboration model between academics, government, and society is used to adderss challenges such as limited funding, reduced trust in formal law, and limited outreach for socialization. In short, the success of sustainable forest and land fire prevention in Sungai Tonang Village, in addition to increasing socio-economic resilience and environmental conservation, depends on cross-sectoral cooperation and the utilization of cultural approaches.